The Effect of Repeated Resveratrol Administration on Global Ischemia-Induced Hippocampal Neurodegeneration, Neurochemical Effects and Functional Alterations - Girbovan, Catrinel (Université d'Ottawa / University of Ottawa, 2015)
Global cerebral ischemia is an established animal model mimicking the effects of cardiac arrest in humans. It is characterized by selective neuronal damage in the hippocampus and significant behavioural and cognitive impairments. In this light, novel therapeutic compounds with numerous physiological targets as well as neuroprotective capabilities and the capacity to lessen residual cognitive deficits pose as great candidates in the treatment of ischemic pathology. The current thesis investigates the possible therapeutic properties of resveratrol (3, 4, 5´trihydroxystilbene), a naturally occurring phytoalexin present in the skin of grapes, against cerebral ischemia-induced neuronal degeneration and cognitive impairments, as well as elaborate on possible mechanisms of action of the compound in male Wistar rats. In Article 1, neuronal density assessment and behavioural testing following chronic pretreatment with resveratrol at two doses (1 and 10 mg/kg) revealed that the compound has important neuroprotective properties at short and long post-ischemic intervals. Despite comparable neuronal protection, the two resveratrol doses showed distinct behavioural effects, highlighting independent actions of the polyphenol on discrete physiological systems mediating cellular survival and behavioural recovery. Articles 2 and 3 investigated possible mechanisms of action of the polyphenol that have not yet been explored with regards to cerebral ischemia. Specifically, Article 2 demonstrated that resveratrol influences markers of plasticity in both ischemic and control animals as well as promotes angiogenesis in the hippocampal region postischemia. Further elaborating on documented effects attributing non-neuronal mechanisms of action of resveratrol in reducing glial activation postischemia, Article 3 highlighted important regulatory effects of resveratrol on mediating glial type-1 glutamate transporter expression at a short reperfusion interval. These findings support the notion of multiple biological targets by resveratrol and highlight its potential role in attenuating forebrain ischemia-induced neuronal degeneration through multiple physiological targets, while cautioning against possible dose-related effects on behaviour and in healthy controls.
Keywords: Cerebral ischemia; Resveratrol; Neuronal degeneration; Behaviour; Rats